"Nove religije? A mislite krščanstvo?" - Črnič, Aleš (Etnolog. Nova vrsta (Ljubljana), 2011)
The article is based on an ethnographic research of contemporary alternative religious and spiritual groups in Slovenia, focusing in particular on so-called "Neo-pagan" groups. Its first part presents Neo-paganism as it flourished in the West in the second half of the 20th century as one of many new religious movements; the central part systematically presents the Neo-pagan and Old Believer groups which have been active in Slovenia in recentyears to suggest a classification in the final part.
Keywords: Slovenci; Slovenes; religion; verovanje; sodobno poganstvo; contemporary paganism; Neo-paganism; neopoganstvo; staroverstvo; Old Belivers; native religion; Slovenia; Slovenija; new religious movements